2009
DOI: 10.1152/jn.00003.2009
|View full text |Cite
|
Sign up to set email alerts
|

Reconfiguration of the Spinal Interneuronal Network During Locomotion in Vertebrates

Abstract: Within the spinal cord, the vast network of excitatory and inhibitory interneurons must be functionally reconfigured on an ongoing basis during locomotion to adapt to the environment and meet particular demands of the task. It is clear that different rhythmic motor behaviors are generated by shared and specialized circuitry and that reconfiguration is governed by multiple inputs that dynamically interact at the spinal level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 9 publications
(30 reference statements)
0
9
0
Order By: Relevance
“…Although they share much of the same locomotor circuitry they may be activated by quite different descending drives. For example, in Xenopus tadpoles, different types of excitatory neurons within the hindbrain are activated during swimming and struggling, with different discharge properties, suggesting that separate excitatory drives mediate the two locomotor behaviours (Li et al 2007; Frigon, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Although they share much of the same locomotor circuitry they may be activated by quite different descending drives. For example, in Xenopus tadpoles, different types of excitatory neurons within the hindbrain are activated during swimming and struggling, with different discharge properties, suggesting that separate excitatory drives mediate the two locomotor behaviours (Li et al 2007; Frigon, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to swimming, the pathways activating struggling require summation of weak synaptic excitation. Most neurons active in swimming are also active in struggling but new neuron types are also recruited and the main excitatory interneurons that drive swimming (dINs) fire weakly if at all (see Berkowitz et al, 2010; (Frigon, 2009)). Struggling is driven by glutamate excitation and glycine inhibition.…”
Section: Strugglingmentioning
confidence: 99%
“…We have identified the main categories of spinal neuron by morphology and, with one exception (K-A cells), defined their properties and functions for one stage of development in Xenopus . At least some of the homologies between interneurons in fish and mammals are beginning to emerge (Frigon, 2009; Goulding, 2009) and we look forward to being able to find the transcription factors expressed by more of the Xenopus spinal interneurons. By identifying the excitatory interneurons that drive swimming and showing that their population extends into the hindbrain, we have been able to explore how the brain controls swimming locomotion.…”
Section: Final Commentmentioning
confidence: 99%
“…It is now well accepted that changes in spinal cord circuitry, both rostral and caudal to an injury, as well as changes in supraspinal structures underpin spontaneous recovery (Beattie et al, 1997;Rose, 2009, 2011;Fouad et al, 2001;Hill et al, 2001;Lawrence and Kuypers, 1968;Oudega and Perez, 2012;Weidner et al, 2001). Recent experiments using a dual lesion model of SCI in cats have shown that recovery of hindlimb locomotion depends on plasticity in spared descending pathways, and within spinal circuits caudal to the lesion (Barriere et al, 2008;Frigon, 2009;Martinez et al, 2011). Further, anatomical studies in rodent models of incomplete SCI have shown that both intact and damaged axons in the vicinity of a spinal lesion sprout to form new intraspinal circuits (Bareyre et al, 2004;Beattie et al, 1997;Courtine et al, 2008;Fouad et al, 2001;Goldshmit et al, 2008;Goldstein et al, 1997;Onifer et al, 2011;Rank et al, 2014).…”
Section: Introductionmentioning
confidence: 99%